BRIEF 3 – Assessing the soil health of three goat farming districts in Nepal: Insights for improved farm management - Giles, James Edward; Otieno, Mary Atieno; Caulfield, Mark E.; Poudel, Avash (2023)
This brief identifies promising soil management practices based on the soil characteristics and current management practices of cooperatives in three goat farming districts in Nepal.